Sonographic Measurement Fetal Abdominal Circumference and Fetal Abdominal Subcutaneous Tissue Thickness for Predicting Fetal Macrosomia - Theethuch Odthon; Somsri Pitukkijronnakorn; Apichart Chittacharoen (The Royal Thai College of Obstetricians and Gynaecologists, 2015)
Objective:To evaluate the value of the sonographic measurement of fetal abdominal circumference (AC) and fetal abdominal subcutaneous tissue thickness (FASTT) for predicting fetal macrosomia.Material and Method:This prospective study was studied in term singleton pregnant women between February 2013 and January 2014. The fetal AC and FASTT were examined in all cases and fetal deliveries were within 24 hours. The fetal birth weight greater than 4,000 g. is macrosomia. Fetal AC and FASTT cut off values for predicting fetal macrosomia were analyzed.Results:This study included 302 pregnant women with median gestational age of 39 weeks (range 37 - 41). The prevalence of fetal macrosomia was 6.9%. At the cut off values of fetal AC ≥ 36.7 cm and FASTT ≥ 10.0 mm, the sensitivity, specificity, positive predictive value, negative predictive value and accuracy were 95.2% and 81.0%, 93.2% and 86.8%, 51.3% and 31.5%, 99.6% and 98.4% and 93.4% and 86.4%, respectively.Conclusion: The sonographic measurements of fetal AC and FASTT were useful for predicting fetal macrosomia.